Aplikasi Stepping Stone Method (SSM) dalam Pengoptimalan Biaya Transportasi Pengiriman Barang di PT. Selatanjaya Aditama Perkasa - Meidiani Sandra; Dony Permana (Journal of Mathematics UNP, 2018)
Abstract - A company distributors usually have constraint to delivery of the goods to the shop or the supermarket. These limitations include the delivered goods must be timely, demand for goods in the store can't be delivered in a single shipment or in the once a time. Therefore it needs a method of transportation to solve this problem. This research aims to know the completion of delivery of the goods on the transportation problem. The method used is the Least Cost Method is one method of transport that produce solutions of the initial shipping costs and Stepping Stone Method is one of the advanced method that can optimize the costs of delivery of the goods. The data used in this research is secondary data originating from PT. Selatanjaya Aditama Perkasa in March2018. By using both of these method    retrieved 10,71% cost reduction. This cost is the optimum cost of delivery of the goods due to the cost of shipping goods to PT Selatanjaya Aditama Perkasa in March 2018 is Rp. 12,602,400.